Preparation of Nitrogen and Phosphorus Doped Porous Carbon from Watermelon Peel as Supercapacitor Electrode Material - Chi Yang; Penghui Li; Yumeng Wei; Yanting Wang; Bo Jiang; Wenjuan Wu (Micromachines, 2023)
The use of green and sustainable biomass-derived compounds to obtain excellent electrochemical properties is important to address growing environmental and energy issues. In this paper, cheap and abundant watermelon peel was used as a raw material to successfully synthesize nitrogen-phosphorus double-doped bio-based porous carbon by a one-step carbonization method and explore it as a renewable carbon source for low-cost energy storage devices. The supercapacitor electrode exhibited a high specific capacity of 135.2 F/g at a current density of 1 A/g in a three-electrode system. A variety of characterization methods and electrochemical tests indicate that porous carbon prepared by this simple method has great potential as electrode materials for supercapacitors.